WBL engagement dinner / Aida Khalida Mohamed Idris and Putri Dahlia Ab Rashid - Mohamed Idris, Aida Khalida; Ab Rashid, Putri Dahlia (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
The idea of Hospitality Engagement Dinner 2018 was coined by the Head of Centre of Studies, Associate Prof. Dr. Johanudin Lahap @ Wahab to boost industrial relations between FPHP UiTM Pulau Pinang and the hospitality players in the industry. It was a platform for the faculty to present pool of student talents and potential collaboration for future programs. All the while when the students were sent for internships, the hospitality industry only knew them as MARA students. Hence, by organizing this event the faculty hope to show the industry what other opportunities it has to offer apart from practical training. The event was led by Puan Putri Dahlia Ab Rashid of Culinary Arts & Gastronomy Department and was joint-organized with the Division of Research, Industrial Linkages, Community & Alumni (ICAN) of UiTM Pulau Pinang. After months of dedicated preparations by the committee members, the dinner was successfully held on Friday, 16 November 2018 at Hotel UiTM Pulau Pinang.